Sorption Mechanism, Kinetics, and Isotherms of Di‑n‑butyl Phthalate to Different Soil Particle-Size Fractions - Xiang, Lei; Wang, Xiao-Dan; Chen, Xiao-Hong; Mo, Ce-Hui; Li, Yan-Wen; Li, Hui; Cai, Quan-Ying; Zhou, Dong-Mei; Wong, Ming-Hung; Li, Qing X (Journal of agricultural and food chemistry, 2019)
Di-n-butyl phthalate (DBP) is a prevalent pollutant in agricultural soils due to use of plastic film. This study focused on sorption mechanism, kinetics, and isotherms of DBP to six paddy soil particle-size fractions (i.e., coarse sand, fine sand, coarse silt, fine silt, clay, and humic acid fractions). DBP sorption involved in both boundary layer diffusion and intraparticle diffusion, following pseudo-second-order kinetics. DBP sorption was a spontaneous physical process, which fit the Freundlich model. Hydrophobic and ionic interaction relevant to the organic matter content, cation exchange capacity, surface area, and pore volume of soil fractions played key roles in DBP sorption. DBP was strongly adsorbed to humic acid and the sorption was reversely associated with soil particle sizes. DBP may exhibit higher mobility and bioavailability in a soil-crop system at lower temperature (15 °C), due to the lower log K oc values.